Analysis of the Islamic Character of Religious Studies in Higher Education: A systematic literature review - K, Munawir; Asril, Zainal; Rahman, Amri; Falihin, Dalilul (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2024)
The role of higher education is very strategic in shaping the character of students. Religious courses in higher education are expected to contribute significantly to the development of students' Islamic character, especially amidst the challenges of globalisation and secularisation. However, the implementation of Islamic values in the curriculum is still debatable. For this reason, this article aims to analyse the implementation of Islamic character in religion courses in higher education, identify elements that support and hinder, and provide recommendations for more effective curriculum development. The method used in this research is Systematic Literature Review (SLR) with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. The data collection process was carried out through searching for relevant articles from the Scopus and Google Scholar databases. Inclusion and exclusion criteria were applied to select eligible articles, resulting in 25 articles being analysed. The results of the analysis showed that religion courses have incorporated some elements of Islamic character, such as honesty, responsibility, and social care. However, there are some challenges in its implementation, such as the lack of training for lecturers, teaching materials that are not in accordance with the context, and low student motivation. This analysis concludes that strengthening Islamic character in religion courses in higher education requires a more holistic and integrated approach. Recommendations for curriculum development include lecturer training, development of contextualised teaching modules, and increased interaction between students and the community. The implications of this research are important to improve the quality of higher education in producing generations with Islamic character.